A comparison of Wisconsin area health clubs in regards to participant safety - Lange, Daniel H. (My University, 1986)
This study was designed to determine if there was a difference in levels of safety when comparing multi-purpose facilities (MPS) to YMCA's/YWCA's (YS). A 29-item questionnaire was sent out to 79 membership-dependent health clubs (HCS), 55 responded; 39 YS and 19MPS. Levels of safety analyzed included CPR requirements, risk factor screening, fitness instructor certifications, and response time of an emergency vehicle.
Keywords: Physical fitness centers -- Wisconsin -- Safety measures